Carbamide promoted polyol synthesis and transmittance properties of silver nanocubes. Issue 4 (2nd February 2016) - Zhang, Jing; Wang, Qiang; Zhang, Xiaohui; Wang, Jigang; Guo, Ming; Wiley, Benjamin J.; Li, Chunhong; Hu, Changwen
Abstract : Ag nanocubes of different sizes were rapidly synthesized via a polyol approach promoted by CO(NH2 )2 and the transmittance properties have been detected. Abstract : In this work, silver (Ag) nanocubes with different sizes were rapidly synthesized with a modified HCl-based polyol approach by employing carbamide (CO(NH2 )2 ) as the additive or promoter, which could shorten the reaction time from about 25 h to less than 4 h and the method could be confirmed as facile and robust. In the reaction system, the NH3 molecules play the role of aggregating Ag + and [Ag(NH3 )2 ] + could gradually release Ag +, which in turn results in formation of a more homogeneous product in a short time (50 min–4 h). Some factors affecting the synthesis including the concentration, reaction time and agitator speed have also been investigated, which could be adjusted to control the size, morphology, purity and uniformity of the Ag nanocubes. A mechanism for the rapid synthesis of the Ag nanocubes was proposed. To overcome the lower repeatability of reported methods, we have supplied a robust method to synthesize Ag nanocubes and this procedure may provide a useful guide for the future synthesis of Ag or other metal nanoparticles. The transmittance properties of the different Ag nanocubes have also been detected, which demonstrated that the transmittance of the Au film coupled with the Ag nanocubes is very sensitive to not only the size of the Ag nanocubes but also the thickness of the polyelectrolyte molecular spacer layers.